Application of Electronic Learning and Educators' Challenges In The 21st Century - nive tiken20; Yeni Erita; Rati syafiana PUTRI; Salmiyanti (RADINKA JAYA UTAMA PUBLISHER, 2023)
The scientific object of learning technology is learning. Learning and learning have experienced extraordinary changes and transformations lately, especially at the turn of the millennium and the beginning of the 21st century. The very rapid development of information technology in this century has had a very significant impact on the world of education. The process of transition from the century of industrialization to the century of knowledge demands that every field in life change very quickly and must be able to adapt quickly. Teachers and students, lecturers and students, educators and students, are required to have the ability to teach and learn in the 21st century. This condition is a challenge and demands educators' involvement in the development of learning technology (PTP). This article uses library research. With data sources from journals, research reports, scientific magazines, newspapers, relevant books, seminar results, unpublished scientific articles, sources, a bibliography, video graphics, and so on.